Nurses' difficulties in inter-hospital transport in immediate life support ambulances - Olga Mota (2022)
Introduction: Inter-hospital transport is one of the most challenging nursing care contexts where difficulties arise frequently, assuming, however, as a priority for professional development. Goals: Explore and describe the nurse’s perspective on inter-hospital transport in ambulances of immediate life support. Methods: Qualitative and exploratory-descriptive study. A semi-structured interview was applied to eight nurses, who perform functions in an ambulance of immediate life support in an hospital of the north zone of Portugal. Results: Nurses experience difficulties related to the three phases of inter-hospital transport: i) difficulties related to the decision-making process of transport itself; ii) difficulties related to transport planning; and iii) difficulties related to carrying out the transport. Conclusions: Numerous difficulties linked to decision-making, planning and carrying out transport were highlighted. The need to train the professional team is a fundamental condition to guarantee a safe and successful inter-hospital transport of the person in critical situation. Continuous improvement in the quality of care can only be possible through an efficient and thorough process of identifying the determining factors in transport. Improving communication, adapting the equipment used, identifying and solving intercurrences, minimizing errors and increasing safety, are ways to improve the quality of transport. Promoting and updating protocols and recommendations for inter-hospital transport can contribute to the creation of specific teams and ambulances for this type of transport.